2021
DOI: 10.3390/app11156981
|View full text |Cite
|
Sign up to set email alerts
|

Making Order in User Experience Research to Support Its Application in Design and Beyond

Abstract: The term User Experience (UX) was introduced to define the dynamics of the human-product interaction, and it was thought that design would have been a main recipient of UX research. However, it can be claimed that the outcomes of UX studies were not seamlessly transferred into design research and practice. Among the possible reasons, this paper addresses the fragmentary knowledge ascribable to the field of UX. The authors reviewed the literature analyzing the conceptual contributions that interpret UX, proposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…User experience (UX) design has been defined in a variety of ways by different researchers but the majority of researchers agree that the UX main objective is to improve the interaction between the website and the end-user through continues development process (Kinuthia, 2013). User Experience (UX) abbreviation was developed to capture the behavior of the human interaction toward the product, and it was assumed that UX research would focus on design, However, it might be argued that the findings of UX research have not been easily translated into visual design but it will help us to design a better (UX) design to meet end-user"s needs (Berni & Borgianni, 2021). Developing the user experience is not limited to the visual arts only but it"s important to study the end-user and understand the system design and user-flow to provide a better usability (Lim, Park, & Cho, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…User experience (UX) design has been defined in a variety of ways by different researchers but the majority of researchers agree that the UX main objective is to improve the interaction between the website and the end-user through continues development process (Kinuthia, 2013). User Experience (UX) abbreviation was developed to capture the behavior of the human interaction toward the product, and it was assumed that UX research would focus on design, However, it might be argued that the findings of UX research have not been easily translated into visual design but it will help us to design a better (UX) design to meet end-user"s needs (Berni & Borgianni, 2021). Developing the user experience is not limited to the visual arts only but it"s important to study the end-user and understand the system design and user-flow to provide a better usability (Lim, Park, & Cho, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers like investigated into the correlation between HCI and personal performance and found that flow elicited the best results from users, with the fewest failures and the maximum pleasure with the systems. According to (Berni & Borgianni, 2021) Usability testing is one of the important techniques; the companies use this technique to explore the important information that should be implemented with high conversion for the end-user and can the company can determine the weakness area in the design journey and improve it check figure 6 to understand how user emotions and satisfaction can affect the experience.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the first ones involve the mass reduction and the replacement of materials and components. While the second ones can instead stimulate to rethinking the design entities, e.g., Function, Product Behavior (e.g., Function-Behavior-Structure-FBS-theory [3]), to user-product interaction (e.g., [9]), and to a greater and more rational exploitation of the resources (e.g., TRIZ [10]).…”
Section: Overview About the Design Strategiesmentioning
confidence: 99%
“…"Designing the product considering the user experience" consists of a change in the designer's perspective when designing a product to favour its usability. For this reason, the focus during the initial parts of the design activity is shifted from the structure of the product to the mode of user interaction, depending on the context of use, ergonomics, affective dimension and cognitive experience [9]. 5.…”
mentioning
confidence: 99%